PELAKSANAAN GOOD PENSION FUND GOVERNANCE PADA DPLK BNI (PROGRAM BNI SIMPONI) - Sylvana Grace; Ning Adiasih (Fakultas Hukum Universitas Trisakti, 2021)
In running the BNI Simponi program, in order for this program to be said to have carried out good management, the Financial Institution Pension Fund must contain the principles listed in Article 1 point 2 of the Financial Services Authority Regulation Number 15/POJK.05/2019. The formulation of the problem in this journal is how the implementation of Good Pension Fund Governance in the BNI Simponi Financial Institution Pension Fund owned by Bank Negara Indonesia. The research method used is normative type, descriptive in nature, the main data is secondary data supported by interviews, how to collect data by literature study, qualitative analysis and how to draw conclusions with the deductive method. The results of the research, discussion and conclusion are that the Pension Fund of the Financial Institution of Bank Negara Indonesia has implemented the principles of good Pension Fund Governance even though there are several obstacles experienced. Suggestion: DPLK BNI needs to improve the technology system so that the obstacles experienced can be overcome and the need for cooperation with the government in order to socialize the importance of having a Pension Fund.